Upaya Meningkatkan Minat Membaca Masyarakat Desa Cibeuteung Udik Melalui Program ‘Saung Baca’ - Apriyanti, Dwi; Nabilah, Nurul; Sarinah, Ika; Mufidah, Vika Nurul (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2022)
The purpose of this service is to increase interest in reading for early childhood children in Cibeteung Udik Village, Kp. Mosque Block. As a result of this activity, KKN students were able to complete the program, namely by establishing a 'Saung Baca' and increasing children's interest in reading.